Ambulatory care sensitive diseases/conditions in adult patients. A systematic review - R. N. Shepel; O. M. Drapkina; A. V. Kontsevaya; S. A. Shalnova; M. M. Lukyanov; E. I. Levchenko; D. V. Voshev; V. P. Lusnikov (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To summarize the published data on the nomenclature of ambulatory care sensitive diseases/conditions (ACSCs) in adult patients as one of the tools for a comprehensive assessment of the effectiveness of primary health care (PHC) measures implemented.Material and methods. The study was implemented in 4 following stages: 1 — search for articles by keywords in electronic bibliographic databases; 2 — duplicate elimination; 3 — review of abstracts with an assessment for compliance with the inclusion/exclusion criteria, followed by a search for full-text versions and final selection of publications; 4 — systematization and analysis of data on the ACSCs. Articles published in the period from January 1, 2012 to December 31, 2022 and containing information on ACSC nomenclature were searched in 4 domestic and foreign electronic bibliographic databases (Elibrary, NLM (PubMed), MEDLINE, PreMEDLINE). The PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) system was used in the preparation of the systematic review. Systematization of information on the obtained results was carried out in Microsoft Office Excel 2016 spreadsheets.Results. In total, out of 10898 initially found publications, 11 full-text papers describing studies that fully met the inclusion/exclusion criteria were admitted to stage 4 and were included in the final analysis. In none of the 11 publications was ACSC nomenclature identical to any other publication included in stage 4 of the analysis. Variability in the total number of ACSCs was noted in each of the assessed papers. In 100% of the analyzed publications, the NCAs included chronic obstructive pulmonary disease/chronic bronchitis, heart failure, diabetes, and hypertension. In 91% (10 publications), the ACSCs included angina pectoris, asthma, iron deficiency anemia, dental and oral diseases, urinary tract infections, acute skin infections, and gastroenteritis.Conclusion. The nomenclature of the ACSCs in different countries is characterized by variability due to demographic, epidemiological, organizational, and other features. The conducted systematic review showed that the nomenclature of the ACSCs has not been defined in the Russian Federation. The data obtained in this work can serve as a basis for initiating a project aimed at developing a domestic nomenclature of ACSCs as one of the tools for a comprehensive assessment of the effectiveness of PHC measures implemented.